1987
DOI: 10.1007/bf00124304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the pyrimido-pyrimidine derivative RX-RA 85 on metastatic tumor cell-vascular endothelial cell interactions

Abstract: An important step in the metastatic process is the interaction of blood-borne malignant cells with the vascular endothelium. Among the agents that may interfere with this process are pyrimido-pyrimidines, such as RX-RA 85, developed originally as an antiplatelet agent. Using an endothelial cell momolayer attachment assay we have investigated the effects of RX-RA 85 on tumor cell and endothelial cell properties. Exposure of bovine aortic endothelial cells for 3 h to greater than 4 micrograms/ml RX-RA 85 produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1989
1989
1993
1993

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…We did not find differences in endothelial adhe sive properties when the endothelial cells were grown under various conditions. Al though BAE cells can be modified in their adhesive characteristics by manipulating their cholesterol content [28] or simply by washing the endothelial cell monolayer be fore the assay with buffer [29], we did not observe changes in adhesion in the present study using 13762NF cells.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…We did not find differences in endothelial adhe sive properties when the endothelial cells were grown under various conditions. Al though BAE cells can be modified in their adhesive characteristics by manipulating their cholesterol content [28] or simply by washing the endothelial cell monolayer be fore the assay with buffer [29], we did not observe changes in adhesion in the present study using 13762NF cells.…”
Section: Discussioncontrasting
confidence: 42%
“…Since endothelial cells can change during in vitro growth in their morphology and bio chemistry [27,28], adhesion [28][29][30], ex pression of cell surface glycoproteins [16,17], and extracellular matrix [30], we exam ined the effects of different endothelial cell culture conditions on the adhesion assay. We did not find differences in endothelial adhe sive properties when the endothelial cells were grown under various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We ignore the molecular basis of these effects. Reportedly, these substances at the same time diminished the number of stress fibers, the organization of microfilaments in the peripheral cell cortex and the extent to which ruffling zones were present [11]. The anti-thrombotic effect of DPD is ascribed to synergistic modification of several biochemical pathways [9]: inhibition of platelet cAMP-phosphodiesterase; potentiation of adenosine inhibition of platelet function by blocking reuptake of adenosine by vascular and blood cells; stimulation of prostacyclin production and potentiation of its antiaggregatory activity.…”
Section: Discussionmentioning
confidence: 98%
“…13762NF cells were radiolabeled as described elsewhere [16,24,33] with 0"25 mCi Na[SlCr]O4 (Carrier-free, New England Nuclear, Boston, MA, U.S.A.) per 100mm dish for 3h in DME:F12 containing 5 per cent FBS. In some experiments, tumor cells were incubated for 14-18h with the indicated RA 233 concentrations.…”
Section: Adhesion Assaymentioning
confidence: 99%
“…We have shown that pyrimido-pyrimidines, which can affect growth and cytoskeletal organization of tumor cells [25], interfere with metastatic tumor cellvascular endothelial cell interactions [24] and the growth-promoting activity of epidermal growth factor (EGF) in EGF-responsive tumor cell clones [20]. The pyrimido-pyrimidines, and especially the drug RA 233, have been tested for inhibition of metastasis formation in a number of animal systems with conflicting results [1,14,18,28,40,41].…”
Section: Introductionmentioning
confidence: 99%